TRAVELLING WITH A TYRIAN MERCHANT: Urban Encounters with Christ followers in Rome - Rüggemeier, Jan (Jahrbuch für Antike und Christentum, 2024)
This article revisits the longstanding thesis that merchants were decisive vectors in bringing the early Christ movement from the eastern Mediterranean to Rome. After critically surveying earlier arguments regarding trade routes via Puteoli, it proposes a shift from institutional to individual perspectives through an »avatar model«. By constructing a historically plausible mercator vitri from Roman Tyre - a freedman specializing in glasswares - this study examines the merchant's professional designation, social and legal dependencies, diasporic associations (statio at Puteoli and Rome), and religious practices. Drawing on literary, epigraphic, and archaeological evidence, it demonstrates how glassblowing innovations and Syro-Phoenician trade networks placed such merchants at the heart of Mediterranean commerce. The article argues that, although merchants possessed the mobility and networks conducive to trans-regional communication, the economic and religious entanglements inherent to their profession - along with negative Christian tropes associating trade with greed - render them less likely as primary missionary agents in the mid-1st century CE.